Selected demographic aspects of contemporary migration trends between Croatia and Austria - Mesarić Žabčić, Rebeka (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2022)
After Croatia’s accession to the European Union, a trend of increased emigration of Croatian citizens outside the borders of Croatia was noticed. The aim of this paper is to map selected demographic characteristics of contemporary migration trends between Croatia and Austria in the period from 2013 (Croatia’s accession to the European Union) to 2020. The paper uses classical demographic statistical-mathematical analytical methods in combination with GIS analysis. The paper is based on official Austrian statistics with a focus on Croatian citizens. The spatial framework of the research is the state level and the Austrian NUTS 3 regions (Gruppen von Gemeinden). According to Austrian statistics, a total of 14,011 Croatian citizens emigrated from Austria to Croatia, and a total of 33,127 Croatian citizens immigrated to Austria from Croatia, which means that Croatia recorded a negative overall migration balance compared with Austria (–19,116 Croatian citizens). As a result, Croatia lost an average of approximately 2,730 people a year due to the emigration of Croatian citizens to Austria.
Keywords: Avstrija; Evropska unija; Hrvaška; hrvaški državljani; migracije